2008
DOI: 10.1080/01612840802274651
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Treatment of Depression in Rural Nursing Home Residents

Abstract: Under-diagnosis and under-treatment of depression are major problems in nursing home residents. The purpose of this study was to determine antidepressant use among nursing home residents who were diagnosed with depression using three different methods: (1) the Geriatric Depression Scale, (2) Minimum Data Set, and (3) primary care provider assessments. As one would expect, the odds of being treated with an antidepressant were about eight times higher for those diagnosed as depressed by the primary care provider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Voyer and Martin (2003) contended that antidepressant drugs are underprescribed for older adults due to a lack of recognition of depressive symptoms by health care providers. In a study of 320 randomly selected Iowa nursing home residents (Kerber, Dyck, Culp, & Buckwalter, 2008), the odds of being treated for depression were eight times greater for those who were diagnosed by a primary care provider versus those diagnosed with either the Geriatric Depression Scale (Yesavage et al, 1982-1983) or the Minimum Data Set. These results provide further evidence that depression in older adults is often unrecognized and untreated.…”
Section: Adverse Effects Of Psychotropic Medications In Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Voyer and Martin (2003) contended that antidepressant drugs are underprescribed for older adults due to a lack of recognition of depressive symptoms by health care providers. In a study of 320 randomly selected Iowa nursing home residents (Kerber, Dyck, Culp, & Buckwalter, 2008), the odds of being treated for depression were eight times greater for those who were diagnosed by a primary care provider versus those diagnosed with either the Geriatric Depression Scale (Yesavage et al, 1982-1983) or the Minimum Data Set. These results provide further evidence that depression in older adults is often unrecognized and untreated.…”
Section: Adverse Effects Of Psychotropic Medications In Older Adultsmentioning
confidence: 99%
“…Although psychotropic medications are frequently prescribed to manage behavioral disturbances and psychiatric symptoms, it is imperative that a comprehensive nursing assessment be conducted to identify other potential causes of disruptive behavior, such as delirium, pain, fatigue, hunger, incontinence, and infection. Nonpharmacological interventions, such as reminiscence, activity therapy, and pet therapy, should be thoroughly explored (Kerber et al, 2008). When psychotropic medications are administered, the lowest dosage possible should be used, usually one third to one half the usual dosage of younger individuals, with slow titration upward (Carr, 2005).…”
Section: Adverse Effects Of Psychotropic Medications In Older Adultsmentioning
confidence: 99%
“…These settings may include nursing homes (31, 52, 61, 69, 7477), medical inpatient units (78), or community settings such as senior centers, adult day health, day treatment programs, rehabilitation services and assisted living facilities (16, 52, 69, 74, 79). Research within the nursing home setting could look at risks / benefits and appropriate use of antidepressant treatment in nursing home populations (31, 61, 76) while also focusing on psychosocial interventions and training more mental health providers in nursing home settings (61).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, some scholars suggest that direct care nurse professionals, in general, are well-positioned to perform depression screening because they interact with patients and should be able to observe symptoms on a daily basis (Clibbens & Rylatt, 2008;Koopmans et al, 2010;Kurlowicz & NICHE Faculty, 1997). Other studies however, found that nurse professionals experience considerable difficulty identifying depression in residents (Bagley et al, 2000;Kerber, Dyck, Culp, & Buckwalter, 2008;Mitchell & Kakkadasam, 2011;Teresi et al, 2001) due to a lack of familiarity with the residents (Kohler et al, 2005), ageist attitudes (Choi et al, 2009), and inadequate training of staff in geriatric mental health (Davison et al, 2007).…”
Section: Who Can Assess Residents For Geriatric Depression?mentioning
confidence: 99%
“…Importantly though, any designated discipline among those suitable for the assessment role (e.g., nurse professionals, social workers, psychologists, physicians, etc.) requires proper geriatric mental health and counselling education to be effective (Bagley et al, 2000;Clibbens & Rylatt, 2008;Kerber et al, 2008;Mitchell & Kakkadasam, 2011;Koopmans et al, 2010;Teresi et al 2001).…”
Section: Access To Mental Health Professionals For Residents With Depmentioning
confidence: 99%